Quality wars : the triumphs and defeats of American business - Main, Jeremy, 1929- 4 0 16; 5 (New York : The Free Press, 1994)
In-depth study chronicling the struggles of American industry to bring about large-scale improvements in quality management, including interviews with more than a dozen senior executives.
At head of title: A Juran Institute report.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Total quality management;Total quality management -- United States -- Case studies.;Case studies; 20; 2